Coating of NCM 851005 Cathode Material with Al0@Al2O3 and Subsequent Treatment with Anhydrous HF. Issue 7 (20th January 2020) - Martens, Arthur; Bolli, Christoph; Hoffmann, Anke; Erk, Christoph; Ludwig, Thilo; El Kazzi, Mario; Breddemann, Ulf; Novák, Petr; Krossing, Ingo
Abstract : The volatile alane (H2 AlO t Bu)2 decomposes into amorphous HAlO or Al 0 @Al2 O3 nanoparticles upon heating, depending on the time and temperature. By coating the Ni-rich cathode material NCM851005 with this compound, the NCM's cycling stability and electric conductivity were increased. Thus, the coating not only yielded Al 0 @Al2 O3 nanoparticles but also, by reaction with surface Li2 O/LiOH/Li2 CO3, a Li + conductive LiAlO2 layer. The coatings with 0.3 and 0.1 wt% (H2 AlO t Bu)2, respectively, significantly reduced the resistance build-up to 70/115% after 280 cycles at 1 C (351% without coating). Upon treatment of the 0.3 wt% Al-coating with two equivalents of anhydrous HF, the Al2 O3 and LiAlO2 parts were transformed into a Li[AlO(OH)F] layer, which yielded better capacity retention, retaining the low impedance build-up of only +120% (280 cycles at 1 C). This treatment, however, proved to have the same effect as simply reducing the amount of (H2 AlO t Bu)2 for the coating to 0.1%.